Type I Interferon Receptor Expression in Human Pancreatic and Periampullary Cancer Tissue. Issue 1 (January 2015) - Booy, Stephanie; Hofland, Leo J.; Waaijers, A. Marlijn; Croze, Ed; van Koetsveld, Peter M.; de Vogel, Lisette; Biermann, Katharina; van Eijck, Casper H.J.
<x xml:space="preserve">Abstract</x> Objectives Interferons (IFNs) have several anticancer mechanisms. A number of clinical trials have been conducted regarding adjuvant IFN-α therapy in pancreatic cancer. Type I IFNs exert their effect via the type I IFN receptor (IFNAR-1, IFNAR-2c). The aims of the present study were to determine the type I IFN receptor expression in pancreatic and periampullary cancer tissues and to study its relation with clinicopathological factors. Methods Receptor expression was determined by immunohistochemistry in paraffin-embedded cancer tissue of 47 pancreatic and 54 periampullary cancer patients. Results The results demonstrated that 91.5% of the pancreatic tumors and 88.9% of the periampullary tumors showed expression of IFNAR-1, of which 23.4% and 13.0% were strongly positive, respectively. Regarding IFNAR-2c expression, 68.1% of the pancreatic tumors and 68.5% of the periampullary tumors were positive, of which 4.3% of the pancreatic tumors and none of the periampullary tumors had a strong expression. No statistically significant associations were found between type I IFN receptor expression and clinicopathological factors or survival. Conclusions Type I IFN receptors are expressed in pancreatic and periampullary cancer tissues although with great intertumoral and intratumoral variability. A small proportion of both tumors showed a strong expression of the IFNAR-1; only a very small percentage of the pancreatic tumors showed strong expression of the IFNAR-2c.